Glucose Metabolic Brain Networks in Early-Onset vs. Late-Onset Alzheimer's Disease - Chung, Jinyong; Yoo, Kwangsun; Kim, Eunjoo; Na, Duk L.; Jeong, Yong (Frontiers in Aging Neuroscience, 2016)
Objective: Early-onset Alzheimer’s disease (EAD) shows distinct features from late-onset Alzheimer’s disease (LAD). To explore the characteristics of EAD, clinical, neuropsychological and functional imaging studies have been conducted. However, differences between EAD and LAD are not clear, especially in terms of brain connectivity and networks. In this study, we investigated the differences in metabolic connectivity between EAD and LAD with adopting graph theory measures. Methods: We analyzed 18F-fluorodeoxyglucose-positron emission tomography (FDG-PET) images to investigate the distinct features of metabolic connectivity between EAD and LAD. Using metabolic connectivity and graph theory analysis, metabolic network differences between LAD and EAD were explored. Results: Results showed the decreased connectivity centered in cingulate gyri and occipital regions in EAD, whereas decreased connectivity in occipital and temporal regions as well as increased connectivity in supplementary motor area were observed in LAD, when compared with age-matched control groups. Global efficiency and clustering coefficients were decreased in EAD but not in LAD. EAD showed progressive network deterioration as a function of disease severity, clinical dementia rating scores, mainly in terms of connectivity between cingulate gyri and occipital regions. Global efficiency and clustering coefficients were also decreased along with disease severity. Conclusion: These results indicate that EAD and LAD have distinguished features in terms of metabolic connectivity, with EAD demonstrating more extensive and progressive deterioration.